Impact of organizational change to improve administrative performance in Ministry of housing and urban planning in Sultanate of Oman - Al-Kharusi, Yousif Khamis; Al-Kharusi, Issa Khamis; Al-Kharusi, Zaid Khamis; Al-Kharusi, Sultan Khamis (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to investigate the level of organizational change and administrative performance and the relationship between them from the point of view of the employees of Ministry of Housing and Urban Planning in Sultanate of Oman. (The descriptive correlative method) used in this study, sample consisted of (245) male and female employees, The study concluded that the level of estimates of the study sample came to a high degree on the axis of organizational change as a whole with an average of (3.58), and the level of administrative performance in Ministry of Housing and Urban Planning in the Sultanate of Oman came at a medium degree on the scale as a whole with an average of (3.16), and no statistically significant differences at (0.05) between organizational change and administrative performance in Ministry of Housing and Urban Planning due to the experience variable. It also indicated the significant relationship between the level of organizational change and administrative performance. The study recommended the need for ministry to publish its vision, philosophy, principles, and objectives of the organizational change process, and to give employees enough space to participate in the change process.